Features of legal liability for violation of migration legislation of Ukraine - Drakokhrust, Tetiana; Mazepa, Svitlana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The peculiarities of legal liability for violation of migration legislation of Ukraine are considered in the article. The authors note the list of regulations governing criminal and administrative liability. The authors emphasize that administrative liability for violation of migration legislation of Ukraine has specific characteristics. The reform of administrative liability in the field of migration consists of two elements: direct reform of the system of administrative liability in the field of migration and the content of the Code of Ukraine on Administrative Offenses; other regulations that establish such administrative liability.  It is noted that the further transformation of administrative responsibility is associated with the improvement of the system of administrative penalties, which are a legal form of implementation of this responsibility subject to their expansion.  The authors emphasize that the study of the peculiarities of the application of the last instance of the legislator of the instrument of criminal liability for offenses in the analyzed area deserves special attention.  The authors note that the qualifiers contain liability for the same acts committed in a manner dangerous to the life or health of a person who was illegally transported across the state border of Ukraine, or committed against several persons, or repeatedly or by prior conspiracy by a group of persons or an official using his official position, and shall be punishable by imprisonment for a term of five to seven years with deprivation of the right to hold certain positions or engage in certain activities for up to three years.  The authors concluded that the difference between the composition of the administrative offense in Art.  204-2 of the Code of Ukraine on Administrative Offenses and the composition of a criminal offense in Part 1 of Art.  332-2 of the Criminal code of Ukraine, consists in the certain purpose which characterizes act as a crime.  However, it is very difficult to prove the goal in practice.